Monotongação dos ditongos decrescentes orais [oʊ̯], [eɪ̯], [aɪ̯] e [oɪ̯] na fala e na leitura em voz alta de universitários sergipanos - Souza, Victor Renê Andrade (2022)
The monophthongization of oral falling diphthongs [oʊ̯], [eɪ̯], [aɪ̯], and [oɪ̯] is a productive linguistic phenomenon in Brazilian Portuguese and has been considerably investigated in spontaneous speech from different dialectal regions in Brazil. In order to contribute to studies about this phenomenon in Sergipe, which are incipient (MOTA, 1986; JESUS; SANTOS; SANTOS, 2010), and to the understanding of this phenomenon in the context of reading aloud, in which the constraints of this process have been little explored, we propose an analysis of monophthongization of oral falling diphthongs [oʊ̯], [eɪ̯], [aɪ̯], and [oɪ̯] in the spontaneous speech and in the reading aloud of undergraduate students from Sergipe, using an acoustic methodology that attests our hearing impression through preestablished parameters.We specifically intended to: i) describe the constraints of the process from the visual inspection of the acoustic clues and ii) investigate if the constraints of the process follows the same tendency in the two stylistic contexts given the greater monitoring observed in the reading aloud and the interference of the orthographic. The corpus under study is composed of sociolinguistic interviews with and reading aloud, which are all part of the Displacement 2020 sample, performed by 12 students at the Federal University of Sergipe (UFS). The categorization of the diphthongs were made through a visual inspection of formant transition (BARBOSA; MADUREIRA, 2015; SILVA et al., 2019) through the spectrogram displayed by Praat (BOERSMA, 2001). The analysis is structured into two sections. At first, we described the percentage of monophthongization per diphthong and tested the association of the process with the independent variables traditionally controlled in sociolinguistic studies. Then, we filtered the contexts that simultaneously occur in the spontaneous speech and in the reading aloud samples and developed a comparative analysis. The monophthongization of [oʊ̯] was the most frequent (90%, n = 762), displaying high percentages in all linguistic environments, with sensibility to the context of reading aloud. The monophthongization of [eɪ̯] presented a percentage of monophthongization of 58% (n = 670), with a strong association with the context following the diphthong composed of the tap [ɾ] and of the postalveolar fricatives [ʃ, ʒ], both in the speech and in the reading aloud. The monophthongization of [oɪ̯] was a little different with a percentage of 17% (n = 130), and this may be related to the non-palatalization of the final fricative in the variety spoken in Sergipe, a context that affords monophthongization of this diphthong according to studies undertook in the south region in Brazil (HAUPT, 2011; SILVEIRA, 2019). The monophthongization of [aɪ̯] was the least frequent (14%, n = 168), presenting higher percentages when followed by the postalveolar fricative consonant [ʃ], preserving the diphthongs in the other contexts. From the analysis, we point to the productivity of the acoustic methodology for the description of variable phonological phenomena due to the highest accuracy achieved, but we also highlight the limitations of the reading aloud sample, mostly in respect to the asymmetry of the linguistic contexts under control. The widening of the sample and the control of more paired contexts may widen the explanatory power of the analysis.